The Vision 7 graphic cooperative: building common spaces since associative practices in La Pampa (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This paper analyzes the experience of Vision 7, a cooperative located in Santa Rosa, La Pampa, based on our participation in the Summer School of the Latin American Union of University Extension (ULEU), organized by the Universidad Nacional de La Pampa. The cooperative is based on the principles of the social and solidarity economy which implies economic and political management based on solidarity cooperation and mutual support. We argue that this experience fosters the construction of common spaces and highlights their political and cultural relevance. In this sense, we explain how can contribute to the formation of solidarity networks and promote the development of public policies that address the needs of cooperatives, by initiatives that promote training, visibility, and the production of know-how.
Keywords: common spaces; associative practices; cooperative work; social and solidarity economy; university extension